Digital Transformation for MSMES: From Local to Global - Priadi, Aryaguna Fadlurrahman; Alghifari, Abdul Hafizd; Fachrudin, Tedy; Amanullah, Muhammad Faiz; Mujiastuti, Rully; Sutrisno, Mirza; Meilina, Popy; Nurbaya Ambo, Sitti; Ardharani, Yana (Edumedia Solution, 2025)
In the digital era, Micro, Small and Medium Enterprises (MSMEs) are required to adapt to technology to improve competitiveness in the global market. One effective strategy is the utilization of digital platforms for online product promotion. This webinar and workshop activity aims to provide MSME players with an understanding of the use of CapCut, Canva, and TikTok Shop as digital marketing tools. The webinar discussed the basic theory of digital marketing strategies, while the workshop provided hands-on practice in creating promotional content using the three platforms. Evaluation was conducted through pre-test and post-test to measure the improvement of participants' understanding. The results showed that 70% of participants experienced an increase in understanding, and 85% of participants were satisfied and very satisfied with the material presented. This activity proves that the utilization of digital technology can help MSMEs in increasing their visibility and market reach more broadly.